Collaborative Learning as a Pedagogical Strategy to Foster Interpersonal Communication Skills among Senior High School Students - Insih Indah Wati, Indah Wati; Tri Wahyuni, Kristianingsih; Mei, Bagus Santoso (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2025)
This study investigates the effectiveness of collaborative learning in enhancing interpersonal communication skills among senior high school students in Jember, Indonesia. Using a quasi-experimental design with 120 participants from four classes, the research combined quantitative and qualitative methods. Data were collected through pre- and post-tests using a validated communication skills questionnaire, classroom observations, and student interviews. The findings revealed a significant improvement in communication skills in the experimental group, supported by increased student confidence, peer support, and active listening as reported in interviews. The results align with sociocultural and cooperative learning theories, emphasizing the role of structured peer interaction in skill development. This study contributes to both theory and practice by providing empirical support for collaborative learning as a strategy to foster essential 21st-century communication competencies. Recommendations include integrating collaborative learning into classroom practice and providing teacher training to maximize its pedagogical impact.